An integrative framework of early socio-emotional competencies: cognition, regulation and communication - Gómez Muzzio, Esteban; Strasser, Katherine (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2022)
Currently there is no consensus on what is the socio-emotional development, what are its components and path of progress, hindering the progress of transdisciplinary research and the development of evaluation and intervention methods in public policies. The literature about socio-emotional development is extensively reviewed, offering a theoretical model that identified three principal socio-emotional competencies: (a) socio-emotional cognition: composed by the attention and interpretation of social situations; (b) emotion regulation: composed by the emotion modulation and impulse control; (c) socio-emotional communication: composed by verbal and no verbal communication with others.